國民核心素養與高中課程發展The Development of Integration of Key Competence into the Senior High School Curriculum - 林永豐 Yung-Feng Lin; 郭俊呈 Chun-Cheng Kuo (Higher Education Foundation, 2013)
本研究旨在說明如何依據後期中等教育階段之核心素養，融入普通高中各學科 課程綱要，進而建構各學科課程之核心素養指標，以達成「K-12年級一貫課程綱要」的「核心素養」之「垂直銜接」與「水平統整」，並做為進一步擬訂「十二年一貫課程體系指引」之基礎。本研究透過文件分析與德懷術探討現行普通高中課程各學科與核心素養之對應關係，以瞭解如何將核心素養融入各學科課程中，達至學科課程與核心素養之課程統整。本研究結論有三，包括：一、普通高中各學科與核心素養的相關性高，應強化核心素養的培養與精進；二、普通高中各學科課綱中所列之核心能力與國民核心素養九個項目有對應之處，亦有不足之處；三、普通高中教育向來重視學科知能的教學，應調整為內容與能力兼具的課程取向。本研究建議：一、依據核心素養的理念，建議重新檢討並修正各科之課程目標與核心能力；二、宜進一步針對尚未分析之六科進行核心素養之分析；三、納入更多各學科專家與實務教師，討論並修正各科之核心素養等。This paper aims to elaborate how can the key competences for upper secondary education stage be integrated into the curriculum of senior high schools. Moreover, it is hoped that indicators of key competences in different subjects can be built up so that key competences for the K-12 grades curriculum could be established being both vertically coherent in different grades and horizontally integrated with other academic subjects. This study adopt document analysis and the Delphi technique as main research methods with particular focus on the relationship between key competences and main subjects in the senior high school curriculum. Three main conclusions are summarized as follows. First, there is a strong relationship between the key competences and the academic subjects in senior high schools. As a result, the key competences can be further enhanced through senior high school curriculum. Second, some key competence are less highlighted in current senior high school curriculum. Third, senior high school curriculum highlights conventionally on academic subject matters. It is highlighted through the comparison with the key competences that a pedagogic focus on key competences can also be integrated. Furthermore, based on the above research three recommendations are also proposed. First, the curriculum guidelines for each subjects should be reviewed and modified. Second, six subjects which have not yet analyzed are suggested to be put under review in the near future. Third, more subject experts and practitioners are recommended to be included for more in-depth investigation into the key competences of senior high school subjects.